2021
DOI: 10.1061/(asce)gt.1943-5606.0002504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monopile Installation on Subsequent Lateral Response in Sand. II: Lateral Loading

Abstract: Monopiles under in-service conditions are subjected to lateral forces and resultant bending moments from the offshore environment. The subsequent lateral response following installation is significantly influenced by the 'initial' soil state post-installation, which is influenced by the pile installation process as demonstrated in previous numerical studies. To date, there are no technical guidelines established for consideration of installation effects on the design of laterally loaded monopiles. This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The findings highlight the differences between the original in situ soil state and that at the end of pile installation. These differences will have an important influence on the inservice lateral pile response as discussed in the companion paper (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The findings highlight the differences between the original in situ soil state and that at the end of pile installation. These differences will have an important influence on the inservice lateral pile response as discussed in the companion paper (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Pile installation leads to less marked changes in soil state than those reported here. This was demonstrated through pile installation analysis using a second pile geometry with D = 8 m and D/t = 80, with the effect on the lateral response discussed in the companion paper (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved by Fan et al (2019), who performed three direct monotonic push-over tests without stopping the centrifuge on a 50-mm monopile model monotonically jacked at 1g and 100g, and impact-driven at 100g into dry sand of medium density to a depth of 3.1D. Fan et al (2019) claimed that the global lateral response of the monopile was significantly influenced by the method of installation, and this was numerically confirmed by Fan et al (2021b). Fan et al (2021b) also revealed that the effect of the method of installation on the lateral response is affected by the initial density of soil, driving distance, geometry of the monopile, and the level of stress and eccentricity of the load.…”
Section: Introductionmentioning
confidence: 90%
“…[28][29][30]62 Similar observations were made in experimental studies. 63,64 For the low-cycle phase of the HCA model, the Sanisand model (version of 2004) 65 is used. Up to now, the HCA model has been mainly used in combination with hypolasticity with intergranular strain extension.…”
Section: Fe Modelmentioning
confidence: 99%